2023
DOI: 10.1037/tra0001245
|View full text |Cite
|
Sign up to set email alerts
|

Self-positions and narratives facilitating or hindering posttraumatic growth: A qualitative analysis with migrant women of Nigerian descent survivors of trafficking.

Abstract: Objective: The literature on sex trafficking has given a great deal of space to the effects on mental health, while little has been devoted to the stories of survivors. This study aims to explore the first-hand stories of immigrant women of Nigerian descent trafficking survivors, describing a qualitative analysis of psychotherapy sessions with them. Within the theoretical framework of Dialogical Self Theory, we explored and invited into dialogue the I-positions generated when individuals have traumatic experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…The SR perspective was proposed and first adopted by Moscovici (1976) to investigate the intersubjective construction of shared knowledge in everyday life. The term social representations refers to systems of belief, ideas, values, and social practices through which knowledge becomes organized and is made accessible to help individuals orient themselves in their social world and provide them with communication codes to use in their social exchanges (Contarello, 2022;Moscovici, 2000). By SRs, we mean intersubjectively constructed forms of knowledge that serve the purpose of generating a reality shared by the members of a social group and/or society (Jodelet, 1989).…”
Section: Theoretical Framework: Sr Theory and Italian Postcolonial Li...mentioning
confidence: 99%
See 1 more Smart Citation
“…The SR perspective was proposed and first adopted by Moscovici (1976) to investigate the intersubjective construction of shared knowledge in everyday life. The term social representations refers to systems of belief, ideas, values, and social practices through which knowledge becomes organized and is made accessible to help individuals orient themselves in their social world and provide them with communication codes to use in their social exchanges (Contarello, 2022;Moscovici, 2000). By SRs, we mean intersubjectively constructed forms of knowledge that serve the purpose of generating a reality shared by the members of a social group and/or society (Jodelet, 1989).…”
Section: Theoretical Framework: Sr Theory and Italian Postcolonial Li...mentioning
confidence: 99%
“…classes 1, 2, 4, 8, 9, 11) and narratives of the migrants' ability to react and cope with difficulties. While some stories of victimization are perceived as necessary to access services and/or apply for political asylum, there are also alternative narratives that facilitate post-traumatic growth and counter the perception of victimizations (Chiara et al, 2022).…”
Section: Tensions In the Discourse On Migrationmentioning
confidence: 99%
“…Discursive researchers and scholars have extensively studied how speakers in conversations draw from, and orient to interpretative repertoires , to make sense of our responses to each other, and of how their interactions unfold (Wetherell, 1998; Butler and Fitzgerald, 2010; Suoninen and Wahlstrom, 2009). Focusing on the discursive aspects of psychotherapy dialogues has proven useful to understand how helpful and unhelpful therapy conversations unfold (e.g., Chiara and Romaioli, 2021; Chiara et al, 2022; Smoliak et al, 2021; Strong et al, 2008; Strong et al, 2021; Tseliou, 2013).…”
Section: Cultural Background(s) From Within and From Withoutmentioning
confidence: 99%
“…Their results indicated that intrusive thoughts of traumatic experiences can create a resiliency that influences career adaptability in a positive direction. The relationship is moderated by post‐traumatic growth showing that making meaning of traumatic events can shield against the experiencing of negative trauma symptoms (Chiara et al., 2022; Llewellyn‐Beardsley et al., 2019; Pak, 2019). The CCI focuses on meaning‐making of life story events, thus highlighting a trauma‐focused practice in the approach.…”
mentioning
confidence: 99%